Induced pluripotent stem cells biobank perspective: from unresolved barriers to stable production - Remark, Lucie; Kofanova, Olga (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):302